Digital Flipbook as a Learning Media to Improve Visual Literacy for 4th Grade Students at SDN Abdi Negara - Hadiapurwa, Angga; Listiana, Annisa; Efendi, Erika Erviana (Universitas Negeri Padang, 2021)
The current development of technology and information has an effect on the advancement of learning media innovation. One of them is the digital-based flipbook innovation. This research was conducted in an effort to utilize flipbook media in digital form to improve visual literacy of grade 4 elementary school students. The method used is quantitative method. Subjects in this study were students at SD Negeri 1 Abdi Negara. To obtain research data used a survey by filling out a questionnaire. Based on these data, it was found that students were easy to use digital flipbooks, easy to read the text, understood the material presented, felt interested and fun when using digital based flipbooks, and understood the material that was being tested. Based on the results of data analysis, it can be said that this digital-based flipbook can be used as a learning media.